2012
DOI: 10.1645/ge-3032.1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Toxoplasma gondii in Slaughtered Pigs in the State of Pernambuco, Brazil

Abstract: The object of this study was to investigate Toxoplasma gondii antibodies and parasite DNA in pigs in the state of Pernambuco, Brazil. Blood samples were collected from 305 slaughtered pigs in 11 municipalities, and their sera were tested for T. gondii antibodies using the indirect fluorescent antibody test (IFAT, cutoff 1:64); 38 (12.5%) samples were positive. Attempts were made to detect T. gondii DNA in the heart tissue of seropositive pigs using the B 1 gene and PCR; 21 (55.2%) of the 38 hearts were positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 8 publications
3
2
2
Order By: Relevance
“…The overall prevalence of the infection was found to be 32.1%. The result of the present study was much higher than the reports from Brazil (12.5%) using indirect fluorescent antibody tests (IFAT) [35], Central Italy (16.14%) using IFAT [36], Southern Italy (16.3%) [37] using Enzyme-Linked Immunosorbent Assay (ELISA), Serbia (9.2%) [38] and Portugal (15.6%) [39] using modified agglutination test (MAT). In contrast, the present result was lower than the report from Egypt (56.6%) using MAT [40].…”
Section: Discussioncontrasting
confidence: 85%
“…The overall prevalence of the infection was found to be 32.1%. The result of the present study was much higher than the reports from Brazil (12.5%) using indirect fluorescent antibody tests (IFAT) [35], Central Italy (16.14%) using IFAT [36], Southern Italy (16.3%) [37] using Enzyme-Linked Immunosorbent Assay (ELISA), Serbia (9.2%) [38] and Portugal (15.6%) [39] using modified agglutination test (MAT). In contrast, the present result was lower than the report from Egypt (56.6%) using MAT [40].…”
Section: Discussioncontrasting
confidence: 85%
“…The overall detection rate of T. gondii was 18.9% (1033/5462). This result is similar to detection rates in eastern China by PCR methods (18.03% or 75/416) [33] [39] and Brazil (12.5% or 38/296) [40] but lower than that reported in Mexico (50.8% or 218/429) [41] and Italy (57.1% or 12/21) [42]. The signi cant difference in the prevalence of T. gondii infection may come from the geographical distribution, animal species, or different detection methods.…”
Section: Discussionsupporting
confidence: 88%
“…However, the occurrence of toxoplasmosis in pigs found in this study was higher than those observed in previous studies: 36.2% in Paraíba (Azevedo et al 2010); 26.9% in Alagoas (Valença et al 2011); 18.2% in Bahia (Bezerra et al 2009); 12.8% in Mato Grosso (Muraro et al 2010); 12.6% in Paraná (Santos et al 2015) and 12.5% in Pernambuco (Fernandes et al 2012). But was lower than observed in Rio de Janeiro (65.8%; Bonna et al 2006) and Rio Grande do Sul (86.0%; Silva et al 2003).…”
Section: Discussioncontrasting
confidence: 81%